Sensory processing atypicalities and social responsiveness in autism spectrum disorder: the mediation of executive function - Ji, Yue; Zhu, Feng-lei; Yin, Pei-pei; Zeng, Shu-ting; Huang, Zhi (Frontiers in Psychiatry, 2026)
BackgroundIndividuals with autism spectrum disorder (ASD) commonly display challenges in social interaction, executive functioning, and sensory processing. Nevertheless, the interrelationships among these domains are not yet fully understood. This study aimed to elucidate whether sensory processing affects social functioning in children with ASD through the mediating role of executive functioning.MethodsA total of 88 children and adolescents with ASD, aged 7 to 14 years, were enrolled. Parent-reported measures included the social responsiveness scale (SRS; social functioning), the behavior rating inventory of executive function–second edition (BRIEF-2; executive functioning), and the sensory profile–second edition (SP-2; sensory processing). Mediation analysis was conducted to examine the proposed relationships.ResultsThe results indicated that emotional regulation, a component of executive functioning, fully mediated the relationship between sensory avoiding and social responsiveness, whereas it partially mediated the relationship between sensory registration and social responsiveness. Additionally, behavioral regulation, another dimension of executive functioning, partially mediated the effects of both sensory avoiding and sensory registration on social responsiveness. These relationships remained significant after controlling for gender, age, and intelligence.ConclusionThese findings underscore the importance of both sensory processing and executive functioning in the social responsiveness of children with ASD. The results suggest a potential mechanistic framework in which executive functions serve as a mediating factor between sensory processing and social behavior in this population.